GAMBARAN PENGADAAN OBAT E-PURCHASING UNTUK PASIEN PROGRAM RUJUK BALIK DI APOTEK KIMIA FARMA SAMARINDA - Islami, Vita Hani; Ansyori, Achmad Kadri; Helmidanora, Rusdiati (Jurnal Riset Kefarmasian Indonesia, 2023)
Procurement plays an important role in the drug management cycle. Efforts to improve performance and efficiency in the drug procurement process, both for the JKN program and other health programs, procurement of drugs and medical devices must use an e-catalogue. The Refer Back Program (PRB) is BPJS Health's flagship program. Kimia Farma Pharmacy is a network pharmacy for the Refer Back Program. Kimia Farma Samarinda Pharmacy, in the procurement of PRB medicines has used e-purchasing and there are still obstacles found in the procurement system such as long lead times, unavailability of medicines at distributors, and price uniformity resulting in shortages of medicines which have a negative impact on the availability of medicines for patients referral program. This research aims to determine the management of drug availability using e-purchasing for referral program patients at Kimia Farma Samarinda Pharmacy. This research is qualitative research with a case study approach. The research was carried out by collecting primary data obtained through in-depth interviews with respondents who were deemed to know and be involved in the procurement and/or management process of medicines at Kimia Farma Pharmacy No. 114 Samarinda. Secondary data was obtained through observing documents related to drug procurement at Kimia Farma Pharmacy No. 114 Samarinda. Research results obtained from Kimia Farma Pharmacy No. 114 Samarinda show that the level of drug availability at Kimia Farma Pharmacy No. 114 Samarinda is still low (14.33%). The availability of PRB drugs in pharmacies is not sufficient to meet the needs of PRB participants. Drug vacancies are mostly caused by vacancies from distributors. To avoid patients not getting medicine, pharmacies borrow medicine from other Kimia Farma pharmacies or reduce the amount of medicine given to patients.